HUMAN RESOURCE MANAGEMENT STRATEGIES IN PORTS TO ADDRESS OPERATIONAL DIGITALIZATION AND MODERN AUTOMATION IN THE GLOBAL CONTEXT - Dhimas Alamsyah (SOSIOEDUKASI, 2026)
This study is motivated by the rapid advancement of digitalization and automation in the port sector, which has significantly transformed operational systems and human resource management practices. These changes create challenges such as digital competency gaps, organizational resistance, and workforce restructuring. Therefore, this study aims to analyze and formulate effective human resource management (HRM) strategies to address operational digitalization and modern automation in ports within a global context. The research employs a qualitative approach using a literature review method, analyzing relevant academic sources through thematic analysis to identify key patterns and strategic insights. The findings reveal that effective HRM strategies include continuous digital competency development, the implementation of electronic HRM (e-HRM), structured change management, and the integration of technology with human capital. Furthermore, fostering a culture of continuous learning and strengthening collaboration among stakeholders are critical success factors in digital transformation. In conclusion, HRM plays a strategic role as a key driver in ensuring the successful adoption and sustainability of technological transformation in the port industry.